Museu Virtual da Dança: levantamento e categorização do acervo documental na cidade de Belém-PA - LAMARÃO, Anna Karolina de Matos (2018)
This study aimed to conduct a survey of the documentary collection about the field of Art, specifically on Dance. It is necessary to categorize the units and subunits which these documents belong, organize and make them available. It is needed to demonstrate the importance of creating a Virtual Museum of Dance to encourage more researches, projects and exhibitions, take into account the production of professionals from Belém of Pará. Because the specific nature of this research, we achieved through Museology, that is an area of knowledge which deals with the relationship between society and the patrimony with purposes of the communication and preservation of them, subsidies for virtual collection which has the organization based on in the reference defining the identity of social human groups in space and time. Working with Museology inter-related with Dance is to build a regional or national social memory, and also have characteristics of social intervention and as research, preservation and communication, almost unexplored about all potential when it comes to the dissemination of dance in the local context, Belém do Pará.